Evaluasi Kebijakan Penyelenggaraan Pendidikan Gratis Pada Jenjang Sekolah Dasar dan Menengah Pertama - Novi Lovita Sari; Hasim As'ari (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
The purpose of this study is to evaluate the policy of providing free education in Pelalawan Regency. The method in this research is to use a qualitative research type with a case study approach with the research location in the Education and Culture Office of Pelalawan Regency. Data collection in this study was obtained through observation, interviews and documentation which were then analyzed through data analysis. The results showed that in evaluating policies on the provision of free education in Pelalawan Regency by using 6 criteria, the evaluation of Dunn's policies was not optimal. In the implementation of this policy there are still obstacles so that there are still not any that do not comply with the criteria for policy evaluation.